Tibial Fractures in Motorcycle Accidents (Annals of Medical Research, 2021)
Aim: There is a significant increase in motorcycle accidents along with increasing number of motorcyclists in metropols due to heavy traffic. As a result of tibial fracture analysis in motorcycle accidents, we planned to emphasize what to do in order to prevent these fractures.
Keywords: Motorcycle Accident, Tibial Fracture